SISTEM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (Analisis kritis Teori konvergensi di SMA Islam Almaarif Singosari) - Ayu Rizky Amalia; Maskuri Bakri; Mohammad Sulistiono (VICRATINA, 2019)
Islamic education education learning system is very closely related to the teaching and learning process, so that in this study researchers will focus more on the learning system. And the learning system will be analyzed using the theory of convergence. In this study there are several research focuses, namely: (1) What are the innate talents (potential) of the students in the Islamic High School Almaarif Singosari (2) What is the contribution of the environment in developing the potential of students in Almaarif Middle School Singosari (3) How is the potential of students after learning Islamic Religious Education in Middle School Singosari Islam Almaarif. This research is intended to see the efforts of teachers in developing the potential of students and to prove whether the potential possessed by students is derived from congenital factors from birth or environmental factors. This study uses qualitative research with a type of case study research. Data collection techniques used are observation, interview and documentation. It can be seen that innate talents possessed by students are honest spiritual potential, discipline and trust, and environmental contributions covering the treatment of students in maintaining cleanliness of the environment, being honest with counseling teachers, trusting in the responsibilities carried out and the potential gained after learning religious education Islam is by producing cognitive, affective and psychomotor abilities.